INDEXED ASSESSMENT OF PERIODONTAL TISSUE IN PATIENTS WITH EARLY FORMS OF GENERALIZED PERIODONTITIS ON A BACKGROUND OF DIABETES TYPE I DIABETIC CARDIOMYOPATHY - R. Shkrebnyuk (Ukrainian Medical Stomatological Academy, 2015)
Patients with initial signs of generalized periodontitis on a background of diabetes type I diabetic cardiomyopathy and in healthy individuals with generalized periodontitis original - the first degree, for the study of periodontal tissue were determined in comparative perspective periodontal indexes (PMA, PI index bleeding gums, depth of periodontal pockets, tooth mobility, Rtg-index bleeding, loss of epithelial attachment). Proved that the index data estimates in generalized periodontitis patients with early forms of the disease against a background of diabetes type I on the background of diabetic cardiomyopathy prove more intense inflammatory and destructive changes in zuboutrymuyuchyh tissues compared with similar values in healthy individuals. Patients with initial signs of generalized periodontitis on a background of diabetes type I diabetic cardiomyopathy and in healthy individuals with generalized periodontitis original - the first degree, for the study of periodontal tissue were determined in comparative perspective periodontal indexes (PMA, PI index bleeding gums, depth of periodontal pockets, tooth mobility, Rtg-index bleeding, loss of epithelial attachment). Functional overload of capillaries that occurs in periodontitis due to shutdown of the microvasculature (obliteration, sclerosis, ateromatoza, endovaskulit, peryvaskulit, thrombosis), causing degenerative changes in the walls of capillaries and the emergence of fibrous structures. Morphological changes in the gums of patients with chronic generalized periodontitis (GP) against diabetes depend on the severity of the clinical course of diabetes. Along with changes in vascular microcirculation (ICR) gum characteristic GP, there is a diabetes-specific microvascular lesions - microangiopathy. Diabetic microangiopathy, according to the data, represents a generalized damage blood vessels ICR ash patients with chronic henerlizovanyy periodontitis on a background of diabetes, based on the damage to the basement membrane (BM) endothelium navkolosudynnyh cellular structures, culminating sclerosis and Hyalinosis. Therefore, for the objectification of inflammation in periodontal tissues in patients with diabetes mellitus against a background of diabetic cardiomyopathy was asked to examine the state for the purpose zuboutrymuyuchyh periodontal tissue by means of indices. In order to clarify the course of generalized periodontitis on a background of diabetes of the first type, we have examined 163 patients who were on dispensary in endocrinological dispensary m. Lviv. Of the people surveyed 46.62% were men, and women's interest rate was 53.37%. According to outpatients, offset form of diabetes was determined in 29 men (38.1%) and 33 women (37.93%); subcompensated form of diabetes - 34 men (44.74%) and 39 women (44.82%). The smallest subgroup - 10.52% men and 11.49% women were persons with diabetes duration of the course of 1 year, and most numerous subgroup was represented 44.73% 45.97% men and women who have diabetes duration of the course was over 10 years . To compare the prevalence of generalized periodontitis in patients with type I diabetes were examined 93 persons of different age and sex (comparative group), who were treated at the Medical Center Dental LNMU Danylo Galician. To assess periodontal status determination conducted objective hygiene and periodontal indices. Oral hygienic condition assessed by a simplified index of Green-Vermilyona hygiene - OHI-S (Simplified Oral Hygiene Index), (1964). To study the prevalence and intensity of inflammation in the gums, we used a modified method of determining the papillary-marginally-alveolar index (PMA) for C. Parma percentage, (1960). The depth of periodontal pockets (PC) was measured by a probe with millimeter divisions in 6 points in mm. The loss of the tooth-gingival epithelial attachment (PEC) determined using periodontal probe calibrated in millimeters, obrahovuyuchy average for measurements at four points around each tooth, the technique H.F.Biloklytskoyi (2010). To determine the level of severity of dystrophic and inflammatory changes in periodontal tissues used combined periodontal index (RI) proposed by Russel in 1956 to study the extent and nature of resorption mezhalveolyarnyh partitions bone alveolar processes carried out X-ray examination using the panoramic radiography and evaluated data on radiological index Fuch (Rtg). The results of all determinations carry the card to periodontal examination. Proved that the index data estimates in generalized periodontitis patients with early forms of the disease against a background of diabetes type I on the background of diabetic cardiomyopathy prove more intense inflammatory and destructive changes in zuboutrymuyuchyh tissues compared with similar values in healthy individuals.